Seniors in Warsaw and their free time in the context of planning health education - Kobos, Ewa; Sienkiewicz, Zofia; Leńczuk-Gruba, Anna; Parkitna, Joanna (Polish Journal of Public Health, 2010)
Introduction. Health education is one of the methods of influencing the lifestyle of an individual and social groups. The basis for undertaking educational activities is the diagnosis of an individual’s or group’s condition in comparison to the local community and environment. Aim. The main aim of the undertaken research was to determine the preferred forms of spending free time by elderly people residing in Warsaw and to examine what factors affect the choice of spending and organizing free time. Material and methods. The research was conducted in Warsaw in 2008. The criterion of choosing the respondents was the place of residence and the age of 60 and above. An author-devised questionnaire was used. 102 respondents took part in the research. Pearson’s correlation test χ² was used to examine the relation among the chosen variables. Results. In the studied population a passive form of spending free time is preferred. Ninety percent (90%) of the respondents watch television in their free time, about 70% listen to the radio and read books and papers. Half of the respondents do nothing or take a nap. Forty three percent (43%) of the respondents spend free time with their family, 21% with friends, about 1/5 alone. The preferred places for spending free time are: summer house (48%) and home (28%). Culture centers (2%), Third Age Universities (2%) and sports or recreational centers (1%) are not popular places of spending free time. From many ways of spending free time the dominating are: going for walks 64.7% and exercising at home 27.5%. Conclusions. The respondents prefer a receptive form of activity in their free time. The physical activity of the respondents is restricted mainly to walking. The people in question most often spend their free time with family. The preferred places for spending free time are summer house and home. In planning health education in correlation to this group of people it is necessary to undertake actions leading to their activation in different spheres.